1991
DOI: 10.1038/354480a0
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the human retinal degeneration slow gene in autosomal dominant retinitis pigmentosa

Abstract: The murine retinal degeneration slow (rds) gene is a semidominant mutation with a phenotype having rod and cone photoreceptors that develop abnormally and then slowly degenerate. The phenotype is a possible model for retinitis pigmentosa, one of the scores of hereditary human retinal degenerations, which is also characterized by photoreceptor degeneration. We report here three mutations of the human homologue of the rds gene (RDS) that cosegregate with autosomal dominant retinitis pigmentosa in separate famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
139
0
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(141 citation statements)
references
References 14 publications
1
139
0
1
Order By: Relevance
“…Almost 30~ in ADRP patients have one of these mutations in the United States . On the other hand~ it was found that the mutations of peripherin-RDS (retinal degenera-tion slow: 6p12) gene locus cosegregate with ADRP in separate families (Farrar et al, 1991 ;Kajiwara et al, 1991). These facts indicate that some cases of ADRP are due to not only the mutation at rhodopsin gene locus but also at peripherin-RDS gene locus.…”
Section: Discussionmentioning
confidence: 99%
“…Almost 30~ in ADRP patients have one of these mutations in the United States . On the other hand~ it was found that the mutations of peripherin-RDS (retinal degenera-tion slow: 6p12) gene locus cosegregate with ADRP in separate families (Farrar et al, 1991 ;Kajiwara et al, 1991). These facts indicate that some cases of ADRP are due to not only the mutation at rhodopsin gene locus but also at peripherin-RDS gene locus.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we have reported that cones lacking RDS (in the cone-dominant neural retina leucine zipper knockout, nrl 2/2 , background) (7 -9) retain some OS function and structure, albeit abnormal (3,10). This divergence in the role of RDS in rods versus cones is underscored by the observation that mutations in the human Rds gene are associated with a variety of rod-or conedominant blinding retinal diseases, including autosomal dominant retinitis pigmentosa and multiple classes of macular degeneration (11,12). The large variety and severity in RDS-related disease make evaluation of its role in OS biogenesis key to our understanding of photoreceptor cell biology and to the development of rational treatments for multiple forms of retinal degeneration.…”
Section: Introductionmentioning
confidence: 95%
“…Mutations in rhodopsin gene Sung et al, 1991a;Inglehearn et al, 1992;Macke et al, 1993), peripherin/RDS gene (Farrar et al, 1991;Kajiwara et al, 1991) and other candidate genes have been found in patients with RP. In Japan, three families with Thr-17-Met , Glu-181-Lys (Saga et al, 1994), or Pro-347-Leu mutation in the rhodopsin gene, and two families with Cys-214-Ser (Saga et al, 1993) or Asn-244-Lys mutation (Kikawa et al, 1994) in the peripherin/RDS gene have been reported as autosomal dominant RP (ADRP).…”
Section: Introductionmentioning
confidence: 99%